2013
DOI: 10.1371/journal.pone.0064774
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Progression of Atherosclerosis and the Methylated Amino Acids Asymmetric Dimethylarginine and Trimethyllysine

Abstract: ObjectiveWe previously showed that treatment with folic acid (FA)/B12 was associated with more rapid progression of coronary artery disease (CAD). High doses of FA may induce methylation by increasing the availability of S-adenosyl-methionine (SAM). Asymmetric dimethylarginine (ADMA) and trimethyllysine (TML) are both produced through proteolytic release following post-translational SAM–dependent methylation of precursor amino acid. ADMA has previously been associated with CAD. We investigated if plasma levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…However, Krempl et al [ 14 ] demonstrated that ADMA levels in unstable angina pectoris patients were significantly higher than SAP patients, in which “multivessel disease” was considered to reflect complication of vascular lesions. However, the cases in both studies were relatively limited and did not fully consider the complication and severity of vascular lesions, which proven to be related with ADMA levels, [ 15 ] that was higher ADMA could result from more severe vascular lesion. The CAS in both groups had no significant difference in our study, which indicated that ADMA levels should be similar between SAP and ACS patients after eliminating bias from complicated vascular lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, Krempl et al [ 14 ] demonstrated that ADMA levels in unstable angina pectoris patients were significantly higher than SAP patients, in which “multivessel disease” was considered to reflect complication of vascular lesions. However, the cases in both studies were relatively limited and did not fully consider the complication and severity of vascular lesions, which proven to be related with ADMA levels, [ 15 ] that was higher ADMA could result from more severe vascular lesion. The CAS in both groups had no significant difference in our study, which indicated that ADMA levels should be similar between SAP and ACS patients after eliminating bias from complicated vascular lesions.…”
Section: Discussionmentioning
confidence: 99%
“…ADMA and the L-arginine:ADMA ratio has been shown to predict mortality and adverse outcome in a range of cardiovascular disorders [ 5 , 13 - 16 ]. Both preclinical and clinical studies have shown that ADMA has a pathophysiological role in the induction of vascular dysfunction and human cardiovascular disease [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…ADMA and TML are both produced by post-translational SAM-dependent methylation of precursor amino acid via proteolytic release. In patients with established CAD, baseline ADMA and TML was associated with angiographic progression of CAD, but treatment with FA/B12 (± B6) did not alter the levels of neither ADMA nor TML [56].…”
Section: Discussionmentioning
confidence: 88%